Preparation and Thermoluminescence Properties of Polycrystalline Na2SO4/SiO2 composite (Brazilian Journal of Radiation Sciences, 2024)
A sodium sulphate/silica (Na2SO4/SiO2) composite was prepared by a sol-gel procedure using a geode as the silica source. The prepared sample was characterized by XRD, XRF and IR techniques. The Na2SO4/SiO2 has an orthorhombic phase, and an average crystalline size is about 51 nm. Thermoluminescence characteristics of Na2SO4/SiO2 were studied at different parameters. The glow curve resulting from Na2SO4/SiO2 showed one clear peak between 150 oC to 200 oC, depending on the energy. The general peak structure of the TL glow curve remains unchanged as a result of repeated cycles of irradiation at various X–ray energies, and exhibits good linearity over the used exposure. There were no significant changes in the TL reading after ten times of reuse, and the fading was observed at 56% after 15 days of irradiation and after one month about 82.3% of the TL signal was lost, and the value of Zeff of Na2SO4/SiO2 was found to be 13.56.